Assessing the environmental sustainability corridor: Linking natural resources, renewable energy, human capital, and ecological footprint in BRICS. (March 2021) - Nathaniel, Solomon Prince; Yalçiner, Kürşat; Bekun, Festus Victor
Abstract: There are studies on renewable energy, natural resources abundance, and their impact on the environment especially in BRICS countries. However, none of the studies has considered human capital in the nexus, knowing fully well that ecological distortions mainly emanates from human activities. Therefore, this study explores the linkage between natural resource, renewable energy, human capital, and ecological footprint (EF) in BRICS using a battery of advance econometric techniques. The findings from the study, across all models, affirm that economic growth and natural resource increase the EF, renewable energy decreases it, while human capital is not yet at a desirable level as to mitigate environmental deterioration. The country-specific results are in harmony in terms of the deteriorating impact of economic growth, and the abating role of renewable energy on the environment. Further findings suggest a feedback causality between human capital, urbanization, and EF. Policies that can enhance renewable energy consumption, human capital development, natural resource sustainability, and curb urban anomaly are discussed. Highlights: The study explores the linkage between natural resource, renewable energy, human capital, and ecological footprint in BRICS. Economic growth and natural resource increase the ecological footprint. Human capital is not yet at a desirable level as to mitigate environmental deterioration. A feedback causality between human capital, urbanization, and ecological footprint. Renewable energy decreases the ecological footprint.